Hypnotherapy smartphone applications for weight loss: A narrative review - Lin, L.P; Farrahdilla, Hamzah; Aryati, A.; Mardiana, M.; Thwe Aung, M.M.; Nurul Afiedia, R. (2021)
Introduction: Despite the current popularity and potential use of smartphone applications to encourage healthy behaviours, hypnotherapy applications focusing on weight reduction are scarcely available and the credibility of existing ones is of concern. Objective: To compile existing weight-loss hypnotherapy smartphone applications and to evaluate the functionality and information provided in the mobile apps. Methodology: Google Play and Apple's iTunes stores were searched from 20 August 2020 to 20 September 2020 for available hypnotherapy-related applications targeting weight loss. Only free, English applications were included. Applications in which the hypnotherapy was not utilize for weight loss or did not contain any hypnotherapy components were excluded. Results: Of 291 identified applications, 22 met the inclusion criteria and were further reviewed. Fourteen of the apps (63.6%) focused on reducing calorie intake and limiting the intake of fattening and sugary foods through hypnotic suggestions. Most applications delivered hypnotherapy via an audio track (77.3%) and 68% enabled the session to be customized. More than 40% of apps developers claimed to have used a licensed hypnotherapist and 25% contained disclaimers in the descriptions. Additionally, 31 .8% of the classified apps earned high ratings from users (between 4 and S stars). Conclusion: Overall results indicate that weight-loss hypnotherapy applications may be useful as an additional tool to assist conventional weight management strategies. However, several issues regarding the contents and credibility should be highlighted in order to boost the quality and substantiate the effectiveness of weight-loss hypnotherapy apps in future.